Interaction and belongingness in two student-centered learning environments. (2019) - Brouwer, Jasperina; Jansen, Ellen; Severiens, Sabine; Meeuwisse, Marieke
Highlights: We examined interaction and belongingness in two student-centered learning environments. In LCs, belongingness relates directly to academic success. In PBL, peer interaction relates directly to academic success. Mainly focused on a safe environment, belongingness appears more important in LCs. Mainly focused on academic aspects, peer interaction seems more important in PBL. Abstract: Extant research is inconclusive about how student-centered learning might affect peer interactions, teacher interactions, belongingness, and academic success. This study investigates the relationships in two commonly applied types of learning environments: learning communities (LCs) and problem based learning (PBL). Survey data from 425 first-year university students, enrolled in either an LC ( N = 333) or PBL ( N = 92) context, provide the input for path analyses to explore two conceptual models. Belongingness appears more important in LCs, whereas for PBL, formal peer interaction seems more important for academic success, which is consistent with the main focus of the two learning environments. LCs are dominantly focused on creating a safe environment and a PBL context is mainly focused on knowledge construction.